PENGARUH PERMAINAN TANGRAM MODIFIKASI TERHADAP KEMAMPUAN GEOMETRI ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK YARI SCHOOL - Niva Sahada; Setiyo Utoyo; Farida Mayar; Tisna Syafnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to find the effect of tangram games on the geometry abilities of children aged 5-6 years at Yari School Kindergarten. This research approach uses a quantitative method with a Quasi Experiment type. This study is children at Yari School Kindergarten. Sampling uses a purposive sampling technique. The samples used are class B11 as the experimental class and class B2 as the control class with 10 children in each class. The data collection technique uses a test, in the form of 5 statement items and the data analysis technique used in this study is to compare the differences between the two average values, so that a T test is carried out. For data processing, the SPPS application Ver 31 For Windows is used. Based on the post-test hypothesis test, the sig value (2-tailed) is 0.000 <0.05. Thus, it means that there is a significant difference (real) between the tangram game and the treatment given by the teacher on children's geometry abilities. It can be concluded that the modified tangram game has an effect on the geometric abilities of children aged 5-6 years.